四川省凉山彝族自治州彝汉民族3 439名残疾人龋病患病情况调查 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: This study aims to conduct a survey of the oral health status of disabled individuals in Liangshan Autonomous Prefecture in Sichuan province. This study was also conducted to prepare caries prevention planning in the region. METHODS: On the basis of the Oral Health Surveys: Basic Methods of WHO and the Third National Oral Health Epidemiological Sample Survey Scheme, we investigated caries infecting disabled individuals who live in one big city (Xichang city), three counties (Bhutto county, Muli Tibetan autonomous county, and Huili county), and 46 towns and villages of Liangshan Autonomous Prefecture in Sichuan province, by multi-stage stratified and cluster sampling. RESULTS: Among 3 439 disabled individuals, 2 085 were males and 1 354 were females; among these individuals, 815 live in the city and 2 624 live in rural areas. Furthermore, 2 177 were Han natives and 1 262 were Yi natives (ethnic). The caries prevalence rate and mean DMFT of disabled individuals in Liangshan Autonomous Prefecture in Sichuan province were 87.1% and 9.53, respectively. In Yi, the caries prevalence rate and mean DMFT of disabled individuals in Liangshan Autonomous Prefecture in Sichuan province were 85.8% and 9.93, respectively; in Han, the caries prevalence rate and mean DMFT of disabled individuals in Liangshan Autonomous Prefecture in Sichuan province were 87.9% and 9.29, respectively. No significant difference was found in the two groups of native (P>0.05). A very low filling rate of 0.2% was also recorded. CONCLUSION: Disabled individuals from Liangshan Autonomous Prefecture in Sichuan province exhibited a high prevalence of caries in permanent teeth. The oral health status of this special group of disabled individuals should be provided intensive care.